2023
DOI: 10.1186/s13287-023-03306-7
|View full text |Cite
|
Sign up to set email alerts
|

Human adipose tissue-derived small extracellular vesicles promote soft tissue repair through modulating M1-to-M2 polarization of macrophages

Abstract: Background Successful regenerative medicine strategies need the manipulation and control of macrophages’ phenotypic switching. Our previous study indicated that rat and porcine adipose tissue-derived small extracellular vesicles could successfully promote soft tissue repair. However, whether human adipose tissue-derived small extracellular vesicles (h-sEV-AT) showed the same ability to promote soft tissue regeneration and whether adipose tissue-derived small extracellular vesicles (sEV-AT) cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…EVs are small, membrane-bound structures that are released from cells into the bloodstream and play a role in cell-to-cell communication [ 22 ] by transporting and delivering bioactive molecules such as proteins and RNA that contribute to intracellular signalling pathways and regulate functions in recipient cells [ 23 , 24 ]. Studies have shown that PE can alter the molecular composition of EVs, impacting their ability to communicate with other cells and modulate physiological processes [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…EVs are small, membrane-bound structures that are released from cells into the bloodstream and play a role in cell-to-cell communication [ 22 ] by transporting and delivering bioactive molecules such as proteins and RNA that contribute to intracellular signalling pathways and regulate functions in recipient cells [ 23 , 24 ]. Studies have shown that PE can alter the molecular composition of EVs, impacting their ability to communicate with other cells and modulate physiological processes [ 25 ].…”
Section: Introductionmentioning
confidence: 99%